Etika Berkomunikasi Dalam Lingkungan Media Sosial - Siti Fatihah Ashari; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The development of social media directly impacts human order and behavior. The symptoms of this cyber bullying behavior in Indonesia are already very worrying and troubling many people who play social media.  Ethics gives humans the experience of how they live their lives through a series of daily actions. Which means ethics can help human activities to make a decision, how they behave and act in a way that is right for the view in living this life.  A good communication ethic will create a good and harmonious atmosphere and relationship between communities. It is inversely proportional if life occurs without an understanding of communication ethics, there will be misunderstandings that make disputes and disputes that can divide the peace of social life. The development of social media can be said to be rapid because anyone can register and have any social media. Social Media Users can access Social Media anytime and anywhere through the Internet network. The activities that take place on each social media are diverse and start from various ideas in the form of words, photos, videos, and other content models.